Pediatric dog bite injuries of head and neck: An algorithm for the treatment of our clinic - Elif Sanli (Turkish Journal of Plastic Surgery, 2020)
Background: Dog bite injuries are more frequent injuries than they are supposed to be in our country. Aims and Objectives: This study presents our pediatric dog bite injuries of head and neck and a simple algorithm of the treatment. Materials and Methods: A retrospective screening was done of the cases, and data was collected. Descriptive statistical analysis was done about age, sex, type of injury, time of injury, type of dog breed, and closure options. Results: A total of ten children were enrolled to the study. The mean age was 6.4 years, and most of the cases were preschool-aged children. Scalp was the most affected region at head and neck. Pit bull was the only known dog breed. The common time of the injuries was morning. Major injuries were more than minor ones, and they were closed with graft or flaps. Conclusion: We think that dog bite injuries are an important problem in our country. Therefore, further detailed multi-centered studies should be done.